2020
DOI: 10.1038/s41422-020-00409-1
|View full text |Cite
|
Sign up to set email alerts
|

RAB31 marks and controls an ESCRT-independent exosome pathway

Abstract: Exosomes are generated within the multivesicular endosomes (MVEs) as intraluminal vesicles (ILVs) and secreted during the fusion of MVEs with the cell membrane. The mechanisms of exosome biogenesis remain poorly explored. Here we identify that RAB31 marks and controls an ESCRT-independent exosome pathway. Active RAB31, phosphorylated by epidermal growth factor receptor (EGFR), engages flotillin proteins in lipid raft microdomains to drive EGFR entry into MVEs to form ILVs, which is independent of the ESCRT (en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
223
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(267 citation statements)
references
References 82 publications
2
223
2
2
Order By: Relevance
“…Another ESCRT-independent pathway involves active Ras-related protein, Rab31, and the formation of ILVs and exosomes while MVE degradation is avoided [42]. When Rab31 concentration is high in late endosomes, it can encounter active epidermal growth factor receptor (EGFR) which, in turn, activates Rab31 via tyrosine phosphorylation.…”
Section: Box 2: Extracellular Vesicle Biogenesis -Escrt-independent Pmentioning
confidence: 99%
“…Another ESCRT-independent pathway involves active Ras-related protein, Rab31, and the formation of ILVs and exosomes while MVE degradation is avoided [42]. When Rab31 concentration is high in late endosomes, it can encounter active epidermal growth factor receptor (EGFR) which, in turn, activates Rab31 via tyrosine phosphorylation.…”
Section: Box 2: Extracellular Vesicle Biogenesis -Escrt-independent Pmentioning
confidence: 99%
“…Aligning with this idea, EGFR signaling has been implicated in the formation of a subtype of very large (1-10 μm) membrane-derived microvesicles termed large oncosomes in prostate cancer cells [27] . Recently, constitutive active EGFR mutants have been found to drive their own secretion by promoting the production of a Rab31 dependent exosome subpopulation [28] . Mechanistically, active EGFR phosphorylates Rab31 on late endosomes, which in turn drives flotillin-dependent ILV formation.…”
Section: Oncogenes and Tumor Suppressors Governing Ev Secretionmentioning
confidence: 99%
“…Passive exosome formation involves the participation of lipids (ceramide), tetraspanins (CD63), and heat shock proteins independently of ESCRT [ 59 , 60 , 61 ]. Studies have shown localization of lipid metabolizing enzyme sphingomyelinase (SMase) and phospholipase D2 (PLD2) to MVB membrane induces the inward curvature required for exosome formation [ 62 , 63 , 64 ].…”
Section: Biogenesismentioning
confidence: 99%